Efl teachers’ perceptions and practices on active listening skill teaching - Contreras Jordán, Rosa; Real Roby, Roddy Andrés; Almache Granda, Gabriela Katherine (Journal of Science and Research, 2022)
Teaching active listening in EFL environments has been a challenge for English teachers. The objective of this quasi-experimental study is to measure how Round table 2.0 changed and enriched teachers´ practice. Twenty-nine EFL teachers with a B2 English proficiency level were the sample, and the data was obtained through a survey and a questionnaire. The research questions were 1. What are the perceptions regarding teaching active listening before and after Round table 2.0? and 2. Which practices have been more effective for EFL listening teaching? According to the surveys, perceptions about teaching active listening before and after the Round Table 2.0 are highly positive. The results showed that the teachers before the training had a low perception of the importance and benefits of active listening and at the same time they did not use specific techniques, presenting a very low frequency. Moreover, according to teachers´ experiences, the most effective active listening strategies were top-down, conversations, podcasts, movies, and series. This study concluded that teachers were not aware of the importance of teaching active listening before the training or the different existed strategies or how to apply them to their lessons. Finally, this study proposes future research regarding authentic resources used to teach active listening to EFL learners.